Metabolic Diffusion in Neuropathologies: The Relevance of Brain-Liver Axis - Vegas-Suárez, Sergio; Simón, Jorge; Martínez-Chantar, María Luz; Moratalla, Rosario (Frontiers in Physiology, 2022)
Chronic liver diseases include a broad group of hepatic disorders from different etiologies and with varying degrees of progression and severity. Among them, non-alcoholic fatty (NAFLD) and alcoholic (ALD) liver diseases are the most frequent forms of expression, caused by either metabolic alterations or chronic alcohol consumption. The liver is the main regulator of energy homeostasis and metabolism of potentially toxic compounds in the organism, thus hepatic disorders often promote the release of harmful substances. In this context, there is an existing interconnection between liver and brain, with the well-named brain-liver axis, in which liver pathologies lead to the promotion of neurodegenerative disorders. Alzheimer’s (AD) and Parkinson’s (PD) diseases are the most relevant neurological disorders worldwide. The present work highlights the relevance of the liver-related promotion of these disorders. Liver-related hyperammonemia has been related to the promotion of perturbations in nervous systems, whereas the production of ketone bodies under certain conditions may protect from developing them. The capacity of the liver of amyloid-β (Aβ) clearance is reduced under liver pathologies, contributing to the development of AD. These perturbations are even aggravated by the pro-inflammatory state that often accompanies liver diseases, leading to the named neuroinflammation. The current nourishment habits, named as Western diet (WD) and alterations in the bile acid (BA) profile, whose homeostasis is controlled by the liver, have been also related to both AD and PD, whereas the supplementation with certain compounds, has been demonstrated to alleviate the pathologies.